ELECTRICAL PROPERTIES OF ANNEALED AND UNANNEALED AL-GE THIN FILM COUPLES - Oluyamo, S S (Biological Sciences - PJSIR, 2004)
The electrical properties of annealed and unannealed Al-Ge thin films had been investigated at electric field values 0.1 - 0.85V/m. Measurements of current - voltage characteristics were obtained at a room temperature. The results of the study showed linear J - V relationship over the voltage range. Annealing changes the electrical properties of the films. As the conductance and barrier heights of annealed samples increase, the saturation current density reduces. Hence a more conducting junction may be obtained from the same metal-semiconductor contact by annealing the sample to a reasonable temperature without loss of surface parameter. In addition, the thickness of the sample also affected the electrical properties of the films.